Primary intradural extramedullary Ewing sarcoma of the cervical spine: A case report and review of the literature. (August 2019) - Tan, Chi Hau; Tan, Darius; Phung, Teik Beng; Lai, Leon T.
Highlights: Spinal ES should be considered in young adults with diffuse intradural extramedullary lesions. Early surgical decompression should be considered to optimise neurological recovery. Gross total resection is often not possible, or necessary, to achieve oncological benefit. Adjuvant radiotherapy can improve overall survival. Abstract: Spinal intradural Ewing sarcoma (ES) of the cervical region is not common. Few cases have been reported and optimal management remain poorly defined. We described a case of a young woman with extensive primary leptomeningeal spinal ES and conducted a review of the literature.